Approximate Solution for Nonlinear Gas Dynamic and Coupled KdV Equations Involving Local Fractional Operator - Jafari, Hossein; Jassim, Hassan Kamil (Sulaimani Journal for Pure and Applied Sciences, 2016)
In this paper, the nonlinear gas dynamic and coupled KdV equations within local fractional operator are discussed. The approximate solutions are obtained by using the local fractional variational iteration method (LFVIM). This method is able to solve large class of linear and nonlinear equations effectively, more easily and accurately; and thus the method has been widely applicable to solve any class of equations in sciences and engineering.
Keywords: Nonlinear gas dynamic equation Coupled Kortewegde Vries Equations Local fractional variational iteration method